Konektivitas Pendidikan SMK PP Negeri Bengkulu, Membangun Masa Depan Berbasis Keterampilan - Sopian Ependi (JPT : Jurnal Pendidikan Tematik, 2025)
Educational connectivity at Vocational High School (SMK) PP Negeri Bengkulu plays an important role in building the future of the young generation based on skills. In facing the challenges of an increasingly competitive world of work, SMK PP Negeri Bengkulu focuses on developing technical skills that are relevant to industry needs. This study aims to analyze how SMK PP Negeri Bengkulu connects skills education with the world of work, and to identify factors that support student success in obtaining the required competencies. With a skills-based approach, SMK PP Negeri Bengkulu is expected to make a significant contribution to the development of a skilled workforce that is ready to compete in the global market. The results of the study show that the connectivity between the education curriculum and industry needs at SMK PP Negeri Bengkulu is vital in creating graduates who are ready to work and contribute to strategic sectors, such as agriculture, engineering, and technology. The success of skills-based education at this vocational school is expected to be a model for the development of vocational education in Indonesia.